2015
DOI: 10.17221/645/2014-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of paper-based food contact materials with different contents of recycled fiber

Abstract: Hladíková Z., Kejlová K., Sosnovcová J., Jírová D., Vavrouš A., Janoušek A., Syčová M., Špelina V. (2015): Microbial contamination of paper-based food contact materials with different contents of recycled fiber. Czech J. Food Sci., 33: 308-312.Recycled paper is commonly used in food packaging industry, especially for disposable products. The material coming into direct contact with food products must not represent a source of contamination for food in accordance with the Framework Regulation (EC) No. 1935 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Earlier research on Food Adulteration and Consumer Awareness in Dhaka City, 1995-2011 found that majority person knew about adulteration and only 9% respondents complained it to the seller and bought pure food from another seller [16]. The present study found [14].…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Earlier research on Food Adulteration and Consumer Awareness in Dhaka City, 1995-2011 found that majority person knew about adulteration and only 9% respondents complained it to the seller and bought pure food from another seller [16]. The present study found [14].…”
Section: Discussionsupporting
confidence: 40%
“…It is also known from several studies that variation of the microorganism of recycling papers might be different for the percentage of their recycling content. [14] found a correlation between recycled matter content and microbial contamination. They took 31 paper samples and found total counts of bacteria ranged from 5.0 × 10 1 to 1.2 × 10 5 CFU/g.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, increasing the proportion of recycled fibres in paper manufacture is associated with an increase in microbial load [25]. pulp, which were found to transfer to gloved hands after drying hands washed with sterile water [26].…”
Section: Discussionmentioning
confidence: 99%
“…Packaging may be contaminated with spoilage or pathogenic microorganisms (Patrignani et al, 2016). Indeed, bacteria and fungi were isolated from paper-based packaging made with recyclable material (Hladíková et al, 2015). Thus, attention should be paid to the material used for packaging since it may act as a source of contamination of food.…”
Section: Risk Factorsmentioning
confidence: 99%